HORIZONTAL MISMATCH AND LABOR MARKET OUTCOMES: EVIDENCE FROM KOSOVO (The South East European Journal of Economics and Business, 2026)
Horizontal mismatch, the misalignment between workers’ fields of study and their current occupations, is a structural issue in Kosovo’s labor market. Evidence on its consequences remains scarce and primarily descriptive. This study analyzes its impact on hourly wages, working hours, quit intentions, and short-term contracts using data from the Kosovo Labor Force Survey (LFS) for 2012–2023. While descriptive statistics and OLS estimates indicate lower wages and slightly higher working hours among mismatched workers, mismatch status may be non-random and subject to endogeneity concerns. To address selection on observables, kernel propensity score matching (PSM) is implemented as the primary estimator. The findings, consistent with existing literature, suggest that mismatched workers earn €0.163 less per hour (6 percent relative to the mean hourly wage) and work 0.374 additional hours per week (0.9 percent relative to the mean weekly hours) compared to adequately matched workers. The estimated effects on short-term contracts (−0.1 percentage points) and quit intentions (+0.3 percentage points) are small and statistically insignificant. Overall, the results suggest that the primary economic cost of horizontal mismatch in Kosovo operates through earnings penalties rather than contractual instability or pronounced dissatisfaction.